2022
DOI: 10.2147/ijgm.s355889
|View full text |Cite
|
Sign up to set email alerts
|

CUL4B is a Potential Novel Prognostic Biomarker and is Correlated with Immune Infiltrates in Malignant Pleural Mesothelioma

Abstract: Background Malignant pleural mesothelioma (MPM) is a particularly fatal cancer with a median survival of less than one year. The value of single-agent checkpoint inhibitors is still obscure in MPM. We aim to reveal CUL4B prognostic role and immune infiltrates in MPM patients. Methods CUL4B expression profile and clinical information of malignant pleura mesothelioma individuals were collected from Gene Expression Omnibus (GEO) and The Cancer Genome Atlas (TCGA) dataset. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 38 publications
(24 reference statements)
0
3
0
Order By: Relevance
“…Our data are also supported by a recent study by Liu, L et al that employed publicly available datasets to identify correlations between CUL4B and the PM tumor microenvironment. The study employed gene expression data from the TCGA and GEO databases to demonstrate significant correlations between CUL4B expression and clinical outcomes and immune cell infiltration [20]. Confirming our previous data, the analyses showed that CUL4B expression was elevated in PM tumor tissue compared to normal pleura, and high CUL4B expression was associated with short the progressionfree survival of PM patient cohorts.…”
Section: Discussionsupporting
confidence: 63%
“…Our data are also supported by a recent study by Liu, L et al that employed publicly available datasets to identify correlations between CUL4B and the PM tumor microenvironment. The study employed gene expression data from the TCGA and GEO databases to demonstrate significant correlations between CUL4B expression and clinical outcomes and immune cell infiltration [20]. Confirming our previous data, the analyses showed that CUL4B expression was elevated in PM tumor tissue compared to normal pleura, and high CUL4B expression was associated with short the progressionfree survival of PM patient cohorts.…”
Section: Discussionsupporting
confidence: 63%
“…Nevertheless, the exact mechanism by which IGFBP3 is engaged in all this is still puzzling. Reportedly, there was a significant correlation between CUL4B and IGFBP3 in mesothelioma [ 14 ]. Besides, CUL4B deficiency affects immune cell function and infiltration [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…The genes encoding a family of genes in this family of proteins form a complex that acts as an intracellular specific linker substrate for enzymatic activity, with a RING‐finger protein polygenic protein 10 . The staining components of several regulators (including quality permitting DNA replication factor 1 in e) 11 …”
Section: Introductionmentioning
confidence: 99%
“… 10 The staining components of several regulators (including quality permitting DNA replication factor 1 in e). 11 …”
Section: Introductionmentioning
confidence: 99%